ANALISIS YURIDIS PENGGUNAAN AKTA CESSIE SEBAGAI SARANA PENGUASAAN ASET PROPERTI OLEH INVESTOR DI INDONESIA - Eka Purnama Witono Ng (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2026)
The property sector in Indonesia plays a vital role in supporting the national economy, but also presents legal challenges related to the management of distressed assets. One of the instruments used by investors to control property assets is the Deed of Assignment, which is the transfer of collection rights from existing creditors to new creditors as stipulated in Article 613 of the Civil Code. This instrument allows investors to obtain rights to receivables secured by property assets, without having to conduct a direct sale and purchase transaction. However, in practice, issues often arise regarding legal protection and enforcement mechanisms for transferred property objects. The formulation of the research problem is: (1) how is the legal regulation of the Deed of Assignment as the basis for the transfer of collection rights in civil agreements in Indonesia, as well as the mechanism for its use in controlling property assets by investors; and (2) how is legal protection for investors if a dispute arises over the transferred property objects. The research method used is normative legal research with a statutory approach and case studies. Data were obtained through a review of literature, laws and regulations, and relevant court decisions, then analyzed qualitatively. The results of the study indicate that the Assignment Deed is valid as a transfer of collection rights, but physical control over the property still requires an execution procedure through a KPKNL auction in accordance with Law No. 4 of 1996 concerning Mortgage Rights. In conclusion, the Assignment Deed provides benefits for investors in obtaining collection rights as well as the potential for asset control, but legal protection still depends on procedural compliance. This study recommends the need for regulatory harmonization and increased legal certainty so that the use of the Assignment Deed is more effective and supports a safe and transparent property investment climate in Indonesia.